Empowering Mosque Management to Strengthen Islamic Moderation Values Based on Ahlussunnah wal Jamaah An-Nahdliyah in Gresik City - Rochmawati, Ida; Saniri, Saniri (LPPM Universitas Yudharta Pasuruan, 2025)
Mosques function not only as places of worship but also as centers for learning and community development. This community service aims to empower mosque administrators in Gresik City to strengthen Islamic moderation values based on Ahlusuannah wal Jamaah An-Nahdliyah, with the goal of preventing the spread of radicalism. Using the Participatory Action Research (PAR) method, the program actively involves mosque administrators and the community in the planning and implementation of activities. Initial findings revealed that some mosque administrators had limited awareness of the risks of radicalism. Following a series of mentoring sessions and focused group discussions, the administrators became more vigilant and successfully developed mosque activity programs rooted in Islamic moderation. Additionally, they began to understand the importance of program sustainability and mosque legal management. This empowerment effort is expected to promote inclusive and harmonious religious practices within the community.